Implicit and explicit drinking identity predict latent classes that differ on the basis of college students' drinking behaviors. (1st September 2017) - Ramirez, Jason J.; Fairlie, Anne M.; Olin, Cecilia C.; Lindgren, Kristen P.
Highlights: We identified latent classes of college students on the basis of drinking behavior. We examined implicit and explicit drinking identity as predictors of classes. Both drinking identity measures predicted overall class membership. Drinking identities are especially strong for high-risk college student drinkers. Drinking identities may be sensitive to past, risky drinking experiences. Abstract: Background: The purpose of this study was to identify distinct classes of college students on the basis of recent and past drinking behaviors and evaluate how implicit and explicit measures of drinking identity predict membership in these classes. Methods: US undergraduate students (N = 456) completed online implicit (Implicit Association Test) and explicit (self-report) measures of drinking identity and assessments of drinking behaviors, including past month drinking, at-risk drinking in the past year, and lifetime history of intoxication. Latent class analysis (LCA) was used to identify classes of college students based on their drinking behaviors. Results: LCA identified five classes: (1) Lifetime Nondrinker, (2) Recent Nondrinker/Past Risk, (3) Light Drinker, (4) Moderate Drinker, and (5) Heavy Drinker. Overall, stronger implicit and explicit drinking identities were uniquely associated with greater odds of belonging to classes with greater alcohol consumption and related consequences relative to those classes characterized by lower alcohol consumption and consequences. Notably, explicit drinking identity was positively associated with odds of membership to the Recent Nondrinker/Past Risk class relative to the Lifetime Nondrinker and Light Drinker classes, and implicit and explicit drinking identities were positively associated with odds of membership to the Heavy Drinker class relative to all other classes. Conclusions: Findings suggest that drinking identity is sensitive to risky drinking experiences in the past, is especially strong among the highest-risk group of college student drinkers, and may be an important cognitive factor to consider as a target for intervention.